A homogenized diamond / silicon carbide composite material and its preparation method and application

The homogenized diamond/silicon carbide composite material prepared through the solvent-thermal process solves the problems of insufficient diamond volume fraction, excessive silicon content and uneven distribution of silicon carbide and silicon in the existing composite materials, achieving higher thermal conductivity and mechanical strength.

CN119118671BActive Publication Date: 2025-02-28辽宁材料实验室
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411624568.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-28
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Among the existing diamond/silicon carbide composite materials, the diamond volume fraction is insufficient and the silicon content is too high, resulting in poor thermal conductivity and mechanical properties. At the same time, the distribution of silicon carbide and silicon is uneven, and the overall performance is poor.

Method used

Using the solvothermal process, a homogenized diamond/silicon carbide composite material is prepared by impregnating diamond particles in the precursor reaction solution, heating gel-curing, carbide and silicon permeation, thereby achieving uniform distribution of silicon carbide and silicon.

Benefits of technology

The volume fraction of diamond is significantly improved, the silicon content is reduced, the uniform distribution of silicon carbide and silicon is achieved, the thermal conductivity and mechanical strength of the composite material are improved, and the overall performance is improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a homogenized diamond / silicon carbide composite material and a preparation method and application thereof, and more specifically, it relates to a homogenized diamond / silicon carbide composite material, based on a solvent thermal process, firstly, diamond particles are impregnated in a precursor reaction solution to obtain a blend of diamond and the precursor reaction solution, then the blend is heated for gel-curing, and then carbonized and siliconized to obtain a homogenized diamond / silicon carbide composite material. The preparation method of the present invention solves the problems of uneven distribution of silicon carbide and silicon and poor comprehensive performance in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a homogenized diamond / silicon carbide composite material and a preparation method and application thereof. Background Art

[0002] Diamond and silicon carbide are two materials with extremely high hardness and excellent thermal conductivity, which are widely used in the field of heat dissipation materials. Due to the increasing demand for heat dissipation in electronic devices and high-power devices, the development of composite materials with higher thermal conductivity and mechanical strength has become a research hotspot.

[0003] Diamond / silicon carbide composites are an ideal heat dissipation material because they combine the high thermal conductivity of diamond with the excellent mechanical properties of silicon carbide. In practical applications, diamond / silicon carbide composites face two major technical challenges: (1) How to increase the volume fraction of diamond in the composite: Due to the excellent thermal conductivity of diamond, increasing the volume fraction of diamond can significantly enhance the thermal conductivity of the material. (2) How to reduce the silicon content: In the process of preparing diamond / silicon carbide composites, silicon carbide is usually generated through the reaction of silicon, but too much silicon will remain in the material, affecting its mechanical properties and thermal conductivity.

[0004] In response to the above problems, technicians in this field have conducted a lot of research and exploration, and proposed a variety of technical solutions to optimize the ratio of diamond to silicon carbide and reduce the content of residual silicon. However, researchers have overlooked the problem of homogenization of silicon carbide and silicon. The homogenization of silicon carbide and silicon can not only improve mechanical properties, but also improve thermal physical properties. Therefore, the homogenization of silicon carbide and silicon is another problem that needs to be solved urgently. Summary of the invention

[0005] The present invention provides a homogenized diamond / silicon carbide composite material and a preparation method and application thereof. The diamond / silicon carbide composite material of the present invention is based on a solvent thermal process. First, diamond particles are impregnated in a precursor reaction solution to obtain a blend of diamond and the precursor reaction solution. Then, the blend is heated for gel-curing, and then carbonized and siliconized to obtain a homogenized diamond / silicon carbide composite material. The composite material solves the problems of uneven distribution of silicon carbide and silicon and poor comprehensive performance in the prior art.

[0006] In a first aspect, the present invention provides a method for preparing a homogenized diamond / silicon carbide composite material, comprising the following steps:

[0007] Step 1 Diamond loading: Load the diamond into the mold;

[0008] Step 2: impregnation: completely immersing the loaded diamond obtained in step 1 in the precursor reaction solution to obtain a blend of diamond and the precursor reaction solution;

[0009] Step 3: gel-curing: heating the blend to gel-curing the blend;

[0010] Step 4: Carbonization: Carbonization and cracking under inert atmosphere to obtain a diamond / carbon blank;

[0011] Step 5: Detection and circulation: Detection step 4 to obtain the carbon content in the diamond / carbon blank. If the target value is not reached, steps 2 to 4 are circulated until the carbon content in the diamond / carbon blank reaches the target value.

[0012] Step 6: Processing: removing the mold outside the diamond / carbon blank and processing the diamond / carbon blank into a desired shape;

[0013] Step 7: siliconizing: siliconizing the diamond / carbon blank obtained in step 6 to obtain a diamond silicon carbide composite material;

[0014] The precursor reaction solution is prepared by uniformly mixing a resin, a solvent A and a solvent B; the solvent A is one or more of ethanol, acetone, ethylene glycol, toluene and xylene, and the solvent B is ammonia water or acetic acid.

[0015] Preferably, in step 1, the particle size of the diamond is in the range of 50 μm to 300 μm.

[0016] Preferably, in step 1, the diamond particle size can be a single particle size, or two or more diamond particle size gradations;

[0017] Preferably, the diamond particle size is graded in a coarse and fine manner, and the volume ratio of coarse and fine diamonds is (60-80): (40-20);

[0018] Preferably, the particle size of the rough diamond is in the range of 100 μm-300 μm;

[0019] Preferably, the fine diamond range is 100 nm-100 μm;

[0020] Preferably, the fine diamond range is 10 μm-60 μm;

[0021] Preferably, the coarse and fine diamonds are mixed mechanically.

[0022] Preferably, the resin is one of phenolic resin, epoxy resin, furan resin, or a combination of one or more of epoxy resin, polyvinyl alcohol, polyvinyl butyral, furan resin, polyurethane and phenolic resin.

[0023] Preferably, the mass ratio of the resin, the solvent A and the solvent B is 1:(0.7-1.5):(0.01-0.1).

[0024] Preferably, in step 2, the loaded diamond is completely immersed in a precursor reaction solution that is more than twice its own volume.

[0025] Preferably, in step 2, the impregnation is carried out under vacuum conditions, the vacuum degree is 0.001 Pa-10 Pa, and the pressure holding time is 5 min-24 h.

[0026] Preferably, in step 2, the impregnation is carried out under vacuum conditions, the vacuum degree is 0.01 Pa-0.2 Pa, and the pressure holding time is 5 min-24 h.

[0027] Preferably, in step 2, the vacuum degree of immersion is 0.05-0.1 Pa, and the holding time is 5 min-24 h.

[0028] Preferably, in step 3, the temperature during gel-curing is 120° C.-280° C., and the mixture is allowed to stand for 1 h-24 h.

[0029] Preferably, in step 3, the temperature during gel-curing is 120° C.-200° C., and the mixture is allowed to stand for 1 h-24 h.

[0030] Preferably, in step 4, the inert atmosphere is nitrogen or argon;

[0031] Preferably, in step 4, the carbonization is carried out by heating the material to a final carbonization temperature of 900° C. to 1200° C. and keeping the temperature for 10 min to 8 h.

[0032] Preferably, in step 4, the carbonization is carried out by heating the material to a final carbonization temperature of 900°C-1000°C and keeping the temperature for 10 min-8 h.

[0033] Preferably, in step 5, the target value is a carbon density of 0.70 g / cm 3 Above, preferably 0.70 g / cm 3 -0.90g / cm 3 .

[0034] Preferably, in step 7, the temperature of the siliconizing process is raised to a siliconizing final temperature of 1420° C.-1800° C. and maintained for 5 min-4 h.

[0035] Preferably, in step 7, the temperature of siliconizing is raised to a siliconizing final temperature of 1500° C.-1650° C. and maintained for 15 min-1 h.

[0036] In a second aspect, the present invention provides a homogenized diamond / silicon carbide composite material prepared by the above preparation method.

[0037] In a third aspect, the present invention provides an application of a homogenized diamond / silicon carbide composite material, wherein the homogenized diamond / silicon carbide composite material is used for heat dissipation materials, wear-resistant materials, electromagnetic shielding materials, biomaterials, catalytic carrier materials, and electrode materials.

[0038] In summary, the present invention has the following beneficial effects:

[0039] 1. The present invention can not only increase the volume fraction of diamond and effectively reduce the silicon content, but also make silicon carbide and silicon evenly distributed in the matrix. By optimizing the material ratio and preparation process, the present invention provides a diamond / silicon carbide composite material with higher thermal conductivity and mechanical strength, which can be applied to the development of high-performance heat dissipation materials.

[0040] 2. The present invention utilizes a solvent thermal (hydrothermal) process to inject pyrolytic carbon between diamond particles, which can achieve precise control of the carbon content between diamond particles. Since pyrolytic carbon has a high degree of uniformity between particles, during the reaction with silicon liquid, it can not only reduce the content of residual silicon, but also make the generated silicon carbide and residual silicon evenly distributed, thereby improving the comprehensive performance of the diamond / silicon carbide composite material.

[0041] 3. The present invention reasonably selects the diamond particle size or particle size grading to prepare blanks with different volume fractions of diamond content, thereby achieving precise control of the diamond content.

[0042] 4. The diamond / carbon blank of the present invention has high strength and can be processed into any size and shape, thereby realizing near-net-shape preparation of the composite material. This processing method not only improves the use value of the high-hardness diamond / silicon carbide composite material, but also makes the material more widely applicable.

[0043] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present disclosure. DETAILED DESCRIPTION

[0044] The present application is further described in detail below with reference to the embodiments.

[0045] Example

[0046] Example 1

[0047] In this embodiment, the specific steps of preparation are as follows:

[0048] Step 1: The diamond particle size is graded in a coarse and fine manner, with a volume ratio of coarse and fine diamonds of 60:40, the particle size of the coarse diamond is 200 μm, and the particle size of the fine diamond is 50 μm; the coarse and fine diamonds are mixed evenly by mechanical mixing and loaded into a graphite mold, and then vibrated and compacted;

[0049] Step 2: completely immerse the loaded diamond obtained in step 1 in a precursor reaction solution of 3 times the volume of diamond, immerse in vacuum, the vacuum degree is 0.02 Pa, and the vacuum pressure is maintained for 6 hours. After the immersion is completed, a blend of diamond and precursor reaction solution is obtained; wherein the precursor reaction solution is a mixture of phenolic resin, solvent A and solvent B, and the mass ratio of phenolic resin, solvent A and solvent B is 1:1.4:0.05; solvent A is ethanol, and solvent B is acetic acid;

[0050] Step 3: placing the mixture of diamond and precursor reaction solution in an oven at 180° C. and heating it for 12 h, so that the mixture in the graphite mold is gel-cured;

[0051] Step 4: In an argon environment, the graphite mold is heated from room temperature to 1000°C at a rate of 2°C / min and kept at this temperature for 1.5 hours for carbonization treatment;

[0052] Step 5 Repeat steps 2 to 4 until the carbon density reaches 0.8 g / cm 3 ;

[0053] Step 6: taking the diamond / carbon blank obtained in step 5 out of the graphite mold and machining it to obtain a diamond / carbon blank of a desired shape;

[0054] Step 7: Place the diamond / carbon body in a graphite crucible, and bury the diamond / carbon body in silicon particles; then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.1 Pa, and the temperature is raised to the final siliconization temperature of 1650°C, and kept warm for 1 hour; after the siliconization is completed, cool with the furnace to obtain a diamond / silicon carbide composite material.

[0055] The thermal conductivity of the diamond / silicon carbide composite material prepared in this embodiment is 621 W / m·K, the Young's modulus is 632 GPa, and the residual silicon content is 6.01 vol%.

[0056] Example 2

[0057] In this embodiment, the specific steps of preparation are as follows:

[0058] Step 1: Diamonds are of a single particle size of 200 μm. The diamonds are placed in a graphite mold and covered and pressed tightly;

[0059] Step 2: completely immerse the loaded diamond obtained in step 1 in a precursor reaction solution of 3 times the volume of diamond, immerse in vacuum, the vacuum degree is 0.02 Pa, and the vacuum pressure is maintained for 6 hours. After the immersion is completed, a blend of diamond and precursor reaction solution is obtained; wherein the precursor reaction solution is a mixture of phenolic resin, solvent A and solvent B, and the mass ratio of phenolic resin, solvent A and solvent B is 1:1.4:0.05; solvent A is ethanol, and solvent B is acetic acid;

[0060] Step 3: placing the mixture of diamond and precursor reaction solution in an oven at 180° C. and heating it for 12 h, so that the mixture in the graphite mold is gel-cured;

[0061] Step 4: In an argon environment, the graphite mold is heated from room temperature to 1000°C at a rate of 2°C / min and kept at this temperature for 1.5 hours for carbonization treatment;

[0062] Step 5 Repeat steps 2 to 4 until the carbon density reaches 0.83 g / cm 3 ;

[0063] Step 6: taking the diamond / carbon blank obtained in step 5 out of the graphite mold and machining it to obtain a diamond / carbon blank of a desired shape;

[0064] Step 7: Place the diamond / carbon blank in a graphite crucible, and bury the diamond / carbon blank in silicon particles. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment. The vacuum degree of the vacuum environment is 0.1 Pa, and the temperature is raised to the final siliconization temperature of 1650 ° C, and the temperature is kept for 1 hour. After the siliconization is completed, the furnace is cooled to obtain a diamond / silicon carbide composite material.

[0065] The thermal conductivity of the diamond / silicon carbide composite material prepared in this embodiment is 578 W / m·K, the Young's modulus is 603 GPa, and the residual silicon content is 5.08 vol%.

[0066] Example 3

[0067] In this embodiment, the specific steps of preparation are as follows:

[0068] Step 1: Diamonds are of a single particle size of 100 μm. The diamonds are placed into a graphite mold and covered and pressed tightly;

[0069] Step 2: completely immerse the loaded diamond obtained in step 1 in a precursor reaction solution of 3 times the volume of diamond, immerse by vacuum, the vacuum degree is 0.001 Pa, and the vacuum pressure is maintained for 24 hours. After the immersion is completed, a mixture of diamond and precursor reaction solution is obtained; wherein the precursor reaction solution is a mixture of phenolic resin, solvent A and solvent B, and the mass ratio of phenolic resin, solvent A and solvent B is 1:1.4:0.05; solvent A is a mixed solvent of ethanol, ethylene glycol and toluene, and solvent B is acetic acid;

[0070] Step 3: placing the mixture of diamond and precursor reaction solution in an oven at 180° C. and heating for 12 hours to allow the mixture in the graphite mold to complete gel-solidification;

[0071] Step 4: In a nitrogen environment, the graphite mold is heated from room temperature to 900°C at a rate of 1°C / min and kept at this temperature for 2 hours for carbonization treatment;

[0072] Step 5 Repeat steps 2 to 4 until the carbon density reaches 0.75 g / cm 3 ;

[0073] Step 6: taking the diamond / carbon blank obtained in step 5 out of the graphite mold and machining it to obtain a diamond / carbon blank of a desired shape;

[0074] Step 7: Place the diamond / carbon blank in a graphite crucible, and evenly place the silicon particles on the diamond / carbon blank; then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.01 Pa, and the temperature is raised to the siliconization final temperature of 1420°C, and kept warm for 4 hours; after the siliconization is completed, cool with the furnace to obtain a diamond / silicon carbide composite material.

[0075] The thermal conductivity of the diamond / silicon carbide composite material prepared in this embodiment is 517 W / m·K, the Young's modulus is 576 GPa, and the residual silicon content is 12.79 vol%.

[0076] Example 4

[0077] In this embodiment, the specific steps of preparation are as follows:

[0078] Step 1: Diamonds are of a single particle size of 100 μm; diamonds are placed into a graphite mold, and the mold is covered and pressed tightly;

[0079] Step 2: completely immerse the loaded diamond obtained in step 1 in a precursor reaction solution of 3 times the volume of diamond, and immerse in vacuum with a vacuum degree of 10 Pa and a vacuum pressure of 5 minutes. After the immersion is completed, a blend of diamond and precursor reaction solution is obtained; wherein the precursor reaction solution is a mixture of phenolic resin, solvent A and solvent B, and the mass ratio of phenolic resin, solvent A and solvent B is 1:1.2:0.05; solvent A is ethylene glycol, and solvent B is acetic acid;

[0080] Step 3: Place the tank in a 280°C oven and let stand for 1 hour to complete gel-curing;

[0081] Step 4: In a nitrogen environment, the graphite mold is heated from room temperature to 1200°C at a rate of 2°C / min and kept at this temperature for 10 min for carbonization;

[0082] Step 5 Repeat steps 2 to 4 until the carbon density reaches 0.81 g / cm 3 ;

[0083] Step 6: taking the diamond / carbon blank obtained in step 5 out of the graphite mold and machining it to obtain a diamond / carbon blank of a desired shape;

[0084] Step 7: Place the diamond / carbon blank in a graphite crucible, and evenly place silicon particles on the diamond / carbon blank; then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.01 Pa, and the temperature is raised to the siliconization final temperature of 1700°C, and kept warm for 0.5 h; after the siliconization is completed, cool with the furnace to obtain a diamond / silicon carbide composite material.

[0085] The thermal conductivity of the diamond / silicon carbide composite material prepared in this embodiment is 463 W / m·K, the Young's modulus is 525 GPa, and the residual silicon content is 10.13 vol%.

[0086] Example 5

[0087] In this embodiment, the specific steps of preparation are as follows:

[0088] Step 1: select coarse diamond with a particle size of 300 μm and fine diamond with a particle size of 60 μm, and mix them in a volume ratio of 70:30; evenly load the mixed diamond into a graphite mold, cover and press tightly;

[0089] Step 2: completely immerse the loaded diamond obtained in step 1 in a precursor reaction solution with a volume twice that of the diamond for 5 hours until the immersion is complete, thereby obtaining a blend of diamond and the precursor reaction solution; wherein the precursor reaction solution is a mixture of a mixed resin, a solvent A and a solvent B, and the mass ratio of the mixed resin, the solvent A and the solvent B is 1:1.5:0.1; the mixed resin is a mixture of a phenolic resin and an epoxy resin, the solvent A is acetone, and the solvent B is acetic acid;

[0090] Step 3: placing the diamond and precursor reaction solution mixture in a 120° C. oven for 24 h to allow the mixture in the graphite mold to complete gel-solidification;

[0091] Step 4: In an argon protective atmosphere, the graphite mold is heated to 900° C. at a heating rate of 2° C. / min and kept at this temperature for 8 h for carbonization treatment;

[0092] Step 5: Repeat steps 2 to 4 until the carbon density reaches 0.84 g / cm³;

[0093] Step 6: taking the diamond / carbon blank obtained in step 5 out of the graphite mold and machining it to obtain a diamond / carbon blank of a desired shape;

[0094] Step 7: Place the diamond / carbon blank in a graphite crucible and bury it in silicon particles. Then, place the graphite crucible in a vacuum sintering furnace for siliconization. Maintain the vacuum degree at 0.05 Pa and raise the temperature to a final siliconization temperature of 1800°C for 5 minutes. After siliconization is completed, cool the blank in the furnace to obtain a diamond / silicon carbide composite material.

[0095] The diamond / silicon carbide composite material prepared in this embodiment has a thermal conductivity of 640 W / m·K, a Young's modulus of 650 GPa, and a residual silicon content of 3.1 vol%.

[0096] Example 6

[0097] Compared with Example 1, the differences are: the phenolic resin is replaced by epoxy resin, and ethanol is replaced by acetone.

[0098] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 650 W / m·K, the Young's modulus is 680 GPa, and the residual silicon content is 4.5 vol%.

[0099] Example 7

[0100] Compared with Example 1, the differences are: the phenolic resin is replaced by a mixture of phenolic resin and polyvinyl alcohol, and the acetic acid is replaced by aqueous ammonia.

[0101] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 690 W / m·K, the Young's modulus is 675 GPa, and the residual silicon content is 6.2 vol%.

[0102] Example 8

[0103] Compared with Example 1, the difference is that the phenolic resin is replaced by a mixture of phenolic resin and polyurethane, and ethanol is replaced by a mixture of toluene and xylene in a mass ratio of 1:1.

[0104] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 705 W / m·K, the Young's modulus is 660 GPa, and the residual silicon content is 7.1 vol%.

[0105] Example 9

[0106] Compared with Example 2, the difference is that the phenolic resin is replaced by a resin mixture of phenolic resin, polyvinyl alcohol, polyvinyl butyral and polyurethane, ethanol is replaced by xylene, and the resin mixture, xylene and acetic acid are mixed in a mass ratio of 1:0.7:0.01.

[0107] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 680 W / m·K, the Young's modulus is 620 GPa, and the residual silicon content is 14.3 vol%.

[0108] Example 10

[0109] Compared with Example 2, the difference is that ethanol is replaced by toluene, and the phenolic resin, toluene and acetic acid are mixed in a mass ratio of 1:1.5:0.1.

[0110] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 695 W / m·K, the Young's modulus is 645 GPa, and the residual silicon content is 12.9 vol%.

[0111] Embodiment 11

[0112] Compared with Example 2, the differences are: ethanol is replaced by a mixed solvent of ethanol, ethylene glycol, toluene and xylene, and the phenolic resin is replaced by a mixed resin of phenolic resin and polyvinyl butyral.

[0113] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 780 W / m·K, the Young's modulus is 475 GPa, and the residual silicon content is 21 vol%.

[0114] Example 12

[0115] Compared with Example 3, the difference is that the phenolic resin is replaced by a mixture of furan resin and phenolic resin, and the carbonization process is to increase the temperature to a carbonization final temperature of 1000°C at a rate of 5°C / min, and then keep the temperature at 1000°C for 2h.

[0116] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 720 W / m·K, the Young's modulus is 525 GPa, and the residual silicon content is 16.5 vol%.

[0117] Example 13

[0118] Compared with Example 3, the difference is that the vacuum degree of immersion is 0.05 Pa and the pressure holding time is 8 h.

[0119] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 450 W / m·K, the Young's modulus is 475 GPa, and the residual silicon content is 2.1 vol%.

[0120] Embodiment 14

[0121] Compared with Example 3, the difference is that the siliconizing process is to increase the temperature to the siliconizing final temperature of 1500° C. and then keep the temperature at 1500° C. for 1 h.

[0122] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 470 W / m·K, the Young's modulus is 495 GPa, and the residual silicon content is 3.5 vol%.

[0123] Embodiment 15

[0124] Compared with Example 4, the difference is that the phenolic resin is replaced by furan resin.

[0125] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 750 W / m·K, the Young's modulus is 475 GPa, and the residual silicon content is 20 vol%.

[0126] The thermal conductivity of the diamond / silicon carbide composite material prepared in the embodiment is 450-780 W / m·K, the Young's modulus is 475-680 GPa, and the residual silicon content is 2.1-21 vol%.

[0127] It can be seen from the results of the above embodiments that the diamond / silicon carbide composite material prepared by the method of the present invention has an extremely low residual silicon content and high thermal conductivity and high Young's modulus, indicating that it not only has good thermal conductivity, but also has excellent mechanical properties.

[0128] Comparative Example

[0129] Comparative Example 1

[0130] Comparative Example 1 The preparation method of the diamond / silicon carbide composite material is:

[0131] Step 1: Wet mix coarse diamond, fine diamond, phenolic resin and ethanol in a ball mill for 2 hours. After wet mixing and ball milling, the mixture is dried in an oven, crushed and sieved to obtain a mixture; wherein the diamond particle size adopts a coarse and fine grading method, the particle size of coarse diamond is 200 μm; the fine diamond is 50 μm, and the volume ratio of coarse and fine diamond is 60:40; the mass of phenolic resin is 20% of the mass of diamond; the mass ratio of phenolic resin to ethanol is 40:60;

[0132] Step 2: Fill the mixture into a 40 mm × 40 mm steel mold and press it at 200 MPa for 5 min.

[0133] Step 3: Carbonizing the green body obtained in step 2 by heating it from room temperature to 1000° C. at a rate of 2° C. / min under an argon environment and keeping the temperature for 1.5 h;

[0134] Step 4: Place the diamond / carbon blank in a graphite crucible, and bury the diamond / carbon blank in silicon particles. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.1 Pa, the siliconization treatment temperature is 1650°C, and the melting time is 1 h. After the siliconization is completed, cool with the furnace to obtain a diamond / silicon carbide composite material.

[0135] After testing, the thermal conductivity of the diamond / silicon carbide composite material prepared in this comparative example is 479 W / m·K, the Young's modulus is 558 GPa, and the residual silicon content is 23.67 vol%. By comparison with Example 1, it can be seen that although the same diamond and adhesive phenolic resin are used, due to the different preparation methods, the thermal conductivity and Young's modulus of the prepared product are lower than those of the product in Example 1 of the present invention, and the residual silicon content is also much higher than that of the product in Example 1.

[0136] Comparative Example 2

[0137] Comparative Example 2 The preparation method of the diamond / silicon carbide composite material is:

[0138] Step 1: Wet-mix diamond, phenolic resin and ethanol in a ball mill for 2 hours. After wet-mixing and ball-milling, the mixture is dried in an oven, crushed and sieved to obtain a mixture; wherein the diamond has a single particle size of 200 μm; the phenolic resin accounts for 20% of the mass of the diamond; and the mass ratio of the phenolic resin to the ethanol is 40:60;

[0139] Step 2: Fill the mixture into a 40 mm × 40 mm steel mold and press it at 200 MPa for 5 min.

[0140] Step 3: Carbonizing the green body obtained in step 2 by heating it from room temperature to 1000° C. at a rate of 2° C. / min under an argon environment and keeping the temperature for 1.5 h;

[0141] Step 4: Place the diamond / carbon blank in a graphite crucible, and bury the diamond / carbon blank in silicon particles. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.1 Pa, the siliconization treatment temperature is 1650 ° C, and the melting time is 1 h. After the siliconization is completed, the furnace is cooled to obtain a diamond / silicon carbide composite material.

[0142] After testing, the thermal conductivity of the diamond / silicon carbide composite material prepared in this comparative example is 421 W / m·K, the Young's modulus is 536 GPa, and the residual silicon content is 32.67 vol%. By comparison with Example 2, it can be seen that although the same diamond and adhesive phenolic resin are used, due to the different preparation methods, the thermal conductivity and Young's modulus of the prepared product are lower than those of the product in Example 2 of the present invention, and the residual silicon content is also much higher than that of the product in Example 2.

[0143] Comparative Example 3

[0144] Comparative Example 3 The preparation method of the diamond / silicon carbide composite material is:

[0145] Step 1: Wet-mix diamond, phenolic resin and mixed solvent in a ball mill for 2 h. After wet-mixing and ball-milling, the mixture is dried in an oven, crushed and sieved to obtain a mixture; wherein the diamond has a single particle size of 100 μm; the mass of the phenolic resin is 30% of the mass of the diamond; the mass ratio of the phenolic resin to ethanol is 40:60; and the mixed solvent is a mixture of ethanol, ethylene glycol and toluene;

[0146] Step 2: Fill the mixture into a 40 mm × 40 mm steel mold and press it at 200 MPa for 5 min.

[0147] Step 3: The green body obtained in step 2 is heated from room temperature to 900° C. at a rate of 2° C. / min in an argon environment and kept at this temperature for 2 h for carbonization;

[0148] Step 4: Place the diamond / carbon blank in a graphite crucible, and place silicon particles on the diamond / carbon blank. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment. The vacuum degree of the vacuum environment is 0.01 Pa, the siliconization treatment temperature is 1420°C, and the temperature is kept for 4 hours. After the siliconization is completed, the furnace is cooled to obtain a diamond / silicon carbide composite material.

[0149] After testing, the thermal conductivity of the diamond / silicon carbide composite material prepared in this comparative example is 390 W / m·K, the Young's modulus is 454 GPa, and the residual silicon content is 23.35 vol%. By comparison with Example 3, it can be seen that although the same diamond and adhesive phenolic resin are used, due to the different preparation methods, the thermal conductivity and Young's modulus of the prepared product are lower than those of the product in Example 3 of the present invention, and the residual silicon content is also much higher than that of the product in Example 3.

[0150] Comparative Example 4

[0151] Comparative Example 4 The preparation method of the diamond / silicon carbide composite material is:

[0152] Step 1: Wet-mix diamond, phenolic resin and ethylene glycol in a ball mill for 2 h. After wet-mixing and ball-milling, the mixture is dried in an oven, crushed and sieved to obtain a mixture; wherein the diamond has a single particle size of 100 μm, the mass of the phenolic resin is 30% of the mass of the diamond, and the mass ratio of the phenolic resin to the ethanol is 40:40;

[0153] Step 2: Fill the mixture into a 40 mm × 40 mm steel mold and press it at 300 MPa for 10 min.

[0154] Step 3: In an argon environment, the green body obtained in step 2 is heated from room temperature to 1200° C. at a rate of 2° C. / min and kept at this temperature for 10 min for carbonization;

[0155] Step 4: Place the diamond / carbon blank in a graphite crucible, and place silicon particles on the diamond / carbon blank. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.01 Pa, the siliconization treatment temperature is 1700°C, and the melting time is 0.5 h. After the siliconization is completed, the furnace is cooled to obtain a diamond / silicon carbide composite material.

[0156] After testing, the thermal conductivity of the diamond / silicon carbide composite material prepared in this comparative example is 356 W / m·K, the Young's modulus is 438 GPa, and the residual silicon content is 20.27 vol%. By comparison with Example 4, it can be seen that although the same diamond and adhesive phenolic resin are used, due to the different preparation methods, the thermal conductivity and Young's modulus of the prepared product are lower than those of the product in Example 3 of the present invention, and the residual silicon content is also much higher than that of the product in Example 3.

[0157] Comparative Example 5

[0158] Comparative Example 5 The preparation method of the diamond / silicon carbide composite material is:

[0159] Step 1: Wet-mix coarse diamond, fine diamond, a mixture of phenolic resin and epoxy resin, and acetone in a ball mill for 1 h. After wet-mixing and ball-milling, the mixture is dried in an oven, crushed, and sieved to obtain a mixture; wherein the diamond particle size adopts a coarse-fine grading method, the particle size of the coarse diamond is 300 μm; the fine diamond is 60 μm, the coarse and fine diamond is 70:30, the mass of the mixture of phenolic resin and epoxy resin is 30% of the mass of the diamond, and the mass ratio of the mixture of phenolic resin and epoxy resin to acetone is 40:60.

[0160] Step 2: Fill the mixture into a 40 mm × 40 mm steel mold, press it at 180 ° C and 50 MPa, and hold the pressure for 10 min;

[0161] Step 3: In an argon environment, the green body obtained in step 2 is heated from room temperature to 900° C. at a rate of 2° C. / min and kept at this temperature for 1 h for carbonization;

[0162] Step 4: Place the diamond / carbon blank in a graphite crucible, and bury the diamond / carbon blank in silicon particles. Then place the graphite crucible in a vacuum sintering furnace for siliconization treatment, the vacuum degree of the vacuum environment is 0.05 Pa, the siliconization treatment temperature is 1800 ° C, and the melting time is 5 min. After the siliconization is completed, cool with the furnace to obtain a diamond / silicon carbide composite material.

[0163] After testing, the thermal conductivity of the diamond / silicon carbide composite material prepared in this comparative example is 561 W / m·K, the Young's modulus is 592 GPa, and the residual silicon content is 17.22 vol%. By comparison with Example 5, it can be seen that although the same diamond and the mixture of the adhesive phenolic resin and the epoxy resin are used, due to the different preparation methods, the thermal conductivity and Young's modulus of the prepared product are lower than those of the product in Example 5 of the present invention, and the residual silicon content is also much higher than that of the product in Example 5.

[0164] By comparing the comparative example with the embodiment, it can be seen that since the comparative example does not use the solvent thermal (hydrothermal) process described in the present invention to inject pyrolytic carbon between diamond particles, but adopts conventional mixing, ball milling, and filling molding methods, it is impossible to achieve precise control of the carbon content between diamond particles; and further, during the reaction with silicon liquid, the residual silicon content is high, and the thermal conductivity and mechanical properties are also weak.

[0165] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a homogenized diamond / silicon carbide composite material, characterized in that: The following steps are involved: Step 1 Diamond loading: Load the diamond into the mold; Step 2: impregnation: completely immersing the loaded diamond obtained in step 1 in the precursor reaction solution to obtain a blend of diamond and the precursor reaction solution; Step 3: gel-curing: heating the blend to gel-curing the blend; Step 4: Carbonization: Carbonization and cracking under inert atmosphere to obtain a diamond / carbon blank; Step 5: Detection and circulation: Detection step 4 to obtain the carbon content in the diamond / carbon blank. If the target value is not reached, steps 2 to 4 are circulated until the carbon content in the diamond / carbon blank reaches the target value. Step 6: Processing: removing the mold outside the diamond / carbon blank and processing the diamond / carbon blank into a desired shape; Step 7: siliconizing: siliconizing the diamond / carbon blank obtained in step 6 to obtain a diamond silicon carbide composite material; The precursor reaction solution is prepared by uniformly mixing a resin, a solvent A and a solvent B; the solvent A is one or more of ethanol, acetone, ethylene glycol, toluene and xylene, and the solvent B is ammonia water or acetic acid; The mass ratio of resin, solvent A and solvent B is 1:(0.7-1.5):(0.01-0.1); In step 3, the temperature during gel-curing is 120°C-280°C, and the mixture is allowed to stand for 1 h-24 h; In step 5, the target value is a carbon density of 0.70 g / cm 3 -0.90g / cm 3 .

2. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: In step 1, the particle size of the diamond is in the range of 50 μm to 300 μm.

3. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: The resin is one of phenolic resin, epoxy resin and furan resin, or a combination of one or more of epoxy resin, polyvinyl alcohol, polyvinyl butyral, furan resin and polyurethane and phenolic resin.

4. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: The impregnation in step 2 is performed under vacuum conditions, the vacuum degree of the vacuum impregnation is 0.001 Pa-10 Pa, and the pressure holding time is 5 min-24 h.

5. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: In step 4, the carbonization is carried out by heating the material to a final carbonization temperature of 900°C-1200°C and then maintaining the temperature at 900°C-1200°C for 10 min-8 h.

6. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: In step 7, the temperature of the siliconizing process is raised to the final siliconizing temperature of 1420°C-1800°C and maintained for 5 min-4 h.

7. The method for preparing the homogenized diamond / silicon carbide composite material according to claim 1, characterized in that: In step 4, the inert atmosphere is nitrogen or argon.

8. A homogenized diamond / silicon carbide composite material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 7.

9. An application of a homogenized diamond / silicon carbide composite material, characterized in that: The homogenized diamond / silicon carbide composite material described in claim 8 is used for heat dissipation materials, wear-resistant materials, electromagnetic shielding materials, biomaterials, catalytic carrier materials, and electrode materials.

Citation Information

Patent Citations

  • Preparation method of diamond-silicon carbide composite material and electronic equipment

    CN110819313A

  • Preparation method of high-thermal-conductivity diamond-silicon carbide multiphase ceramic and heat dissipation substrate

    CN117088690A